Pelatihan Penyelesaian Soal Matematika SD Berbasis Literasi dan Numerasi di Desa Bandar Bireuen - Novianti Novianti; Siti Khaulah; Bulan Nuri; Friantiani Safitri; Marnita Marnita (Aceh Journal of Community Engagement (AJCE), 2022)
The low level of literacy and numeracy skills for elementary school students is something that deserves attention so that it can change the level of children's abilities to be better at strengthening literacy and numeracy. The purpose of this activity is to increase the learning interest of elementary school students from various levels related to literacy and numeracy skills. This activity was carried out in Bandar Bireuen Village by utilizing existing village facilities and places. In addition, the service team from the lecturers and students also brought and provided some reading materials and mathematics learning media that could be used as a reference for children while studying. This activity took place in an orderly manner, the children looked enthusiastic with innovative and fun learning methods so as not to make children get bored quickly in learning. The children's vacation time is utilized by useful activities which are continuously accompanied and facilitated by a team of lecturers and students from the Mathematics Education Study program Almuslim University.